Interpersonal Communication in the Character Building of Students in Islamic Boarding Schools - Dafrizal, Dafrizal; Rohanis, Rohanis; Alfriani, Ranti Dwi; Faizah, Tsamrotul; Yanderi, Ismar (Suluah Pasaman, 2023)
Islamic boarding schools are Islamic institutions that help and develop students from a religious perspective which includes character formation. One of the success factors in forming the character of students in Islamic boarding schools is the role of a teacher. A teacher must be able to communicate well with students by prioritizing student discipline and politeness. One of the communications carried out in developing students is interpersonal communication. This research aims to find out how teachers' interpersonal communication approaches and strategies shape the character of Islamic boarding school students in Indonesia. This research uses a qualitative method with a case study type. Data sources were taken from ten informants through direct interviews using a set of interview protocols. The informants consisted of teachers at Islamic boarding schools and students. All interview data obtained was analyzed thematically using the Milles & Hubberman Interactive Analysis Model technique. Research findings found three identification approaches and two interpersonal communication strategies used by teachers in forming students' characters. The three identification approaches are the cultural approach, the sociological approach, and the psychological approach. The two strategies used by the teacher are punishment and catalyst strategies. This research has revealed teachers' interpersonal communication approaches and strategies in shaping the character of Islamic boarding school students in Indonesia. Apart from that, the results of this research can be used as a reference for anyone who wants to manage an educational institution in the form of an Islamic boarding school.